2020
DOI: 10.1002/jez.b.22986
|View full text |Cite
|
Sign up to set email alerts
|

A putative novel role for Eip74EF in male reproduction in promoting sperm elongation at the cost of male fecundity

Abstract: Spermatozoa are the most morphologically variable cell type, yet little is known about genes controlling natural variation in sperm shape. Drosophila fruit flies have the longest sperm known, which are evolving under postcopulatory sexual selection, driven by sperm competition and cryptic female choice. Long sperm outcompete short sperm but primarily when females have a long seminal receptacle (SR), the primary sperm storage organ. Thus, selection on sperm length is mediated by SR length, and the two traits ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 72 publications
(114 reference statements)
1
17
0
Order By: Relevance
“…In addition, Br-c is reported to be involved in reproductive processes such as vitellogenesis [85], oogenesis [86], and embryogenesis [87] in both insects and crustaceans. Recently, Eip74EF was proposed to be involved in Drosophila spermatogenesis and male fecundity [88]. In the present study, genes coding for proteins involved in the reproductive process were mis-regulated in males exposed to 50 µg/L of TEB.…”
Section: Reproductive Capacity and Vitellogenin Status In Malesmentioning
confidence: 48%
“…In addition, Br-c is reported to be involved in reproductive processes such as vitellogenesis [85], oogenesis [86], and embryogenesis [87] in both insects and crustaceans. Recently, Eip74EF was proposed to be involved in Drosophila spermatogenesis and male fecundity [88]. In the present study, genes coding for proteins involved in the reproductive process were mis-regulated in males exposed to 50 µg/L of TEB.…”
Section: Reproductive Capacity and Vitellogenin Status In Malesmentioning
confidence: 48%
“…We measured 1-7 sperm per male, with an average of 4. These sample sizes are standard (e.g., 24,32) and sufficient to capture variation among males (Fig S5). To measure testis size, we dissected a testis with attached seminal vesicle using fine forceps in 1X PBS and transferred the tissue to 40 μl of PBS, mounted under a cover slip, imaged immediately at 100X under phase contrast, and measured using the segmented line tool in ImageJ.…”
Section: Testis Size and Sperm Lengthmentioning
confidence: 99%
“…22097, 22125) that were originally phenotyped as part of another study in 2019. The standard competitor male derived from a Canton-S stock with a protamine-GFP construct that is expressed in sperm heads as well as an external GFP eye marker for scoring paternity (32). All stocks new to the lab were reared for at least two prior generations on yeast-sugar-agar medium at 23 °C sprinkled with live yeast at moderate densities.…”
Section: Sperm Length and The Post-mating Responsementioning
confidence: 99%
See 1 more Smart Citation
“…E74A , a subtype of the E74 gene, is a key early response gene induced by 20E in the transcription factor cascade and belongs to a member of the E26 transformation‐specific (ETS) family (Fletcher & Thummel, 1995; Sharrocks, 2001; Sharrocks et al, 1997; Sun et al, 2005). Numerous studies have shown that E74 is involved in insect molting, chitin synthesis, growth and development, ecdysone titer, virus infection mechanism, male sperm length, and fertility (Chebbo et al, 2021; Fletcher et al, 1995; Stilwell et al, 2003; Zhang, Yao, et al, 2022;). MsE74A expression was found to be induced by 20E in Manduca sexta , and the expression level remains high during larvae, pupae, and adult molting (Stilwell et al, 2003).…”
Section: Introductionmentioning
confidence: 99%